Pandemics in Human History: A Study of Origin, Enormity, Mortality Rate and Controlling Strategies: Life Sciences-Pandemics - Adya Trisal; Bhoomika Pandey; Dheeraj Mandloi; Tapesh Sarsodia; Sapna Jain Dabade (International Journal of Life Science and Pharma Research, 2022)
With the advent of time, the human population has augmented and so have the transmittable diseases, but not every disease can be branded with the title of being a pandemic. A pandemic is principally an outbreak of a disease affecting a significantly large geographical area and marks the destruction of all life forms. Throughout history, mankind has been afflicted with, and endured several pandemics. These pandemics had various underlying impacts on both social as well as the economic aspects of the affected nations. From devastatingly high death toll to economic collapses, a pandemic causes a plethora of unpropitious effects. But sometimes, the aftermath of a pandemic can also have a positive outcome e like breakthroughs in the field of medicine, immunization and antimicrobial cures, the fact that, the concept of a vaccine was conceived as a repercussion of the smallpox pandemic, is the best example to reinforce this statement. In previous research papers different authors have inculcated distinct methodologies and although these papers were structured immaculately, they lack in terms of information as these papers focus on specific diseases and discuss parameters like death rate, mode of transmission etc. pertaining to those particular pandemics only. This paper on the other hand outlines the most prominent and noteworthy outbreaks (in terms of destruction to life, property and economy) and will help the reader to attain a comprehensive and unobstructed idea about the major pandemics, which have occurred throughout the history. It also provides an in-depth understanding about their timeline, origins, mortality rate and coping strategies as well.